Clinical features and management of 16q24.3 microdeletion KBG syndrome: literature review - Li, Miaomiao; Wang, Shiqi; Pan, Guimei; Zhang, Zixia; Wang, Xi; Hu, Jiaqian; Wang, Mengqin; Du, Mengmeng; Wei, Haiyan; Chen, Yongxing (Frontiers in Pediatrics, 2026)
BackgroundKBG syndrome (KBGS) is an autosomal dominant disorder presenting with diverse clinical features. Although multiple cases of the microdeletion subtype have been reported, discussions regarding its phenotypic characteristics remain relatively limited. This study aims to summarize the clinical features and management strategies for pediatric KBGS patients caused by 16q24.3 microdeletions, thereby enhancing awareness of this rare disease.MethodWe conducted a retrospective analysis of the clinical manifestations, genetic characteristics, and clinical management of four pediatric patients with microdeletion-type KBGS at our institution, and systematically reviewed relevant literature to compile clinical data on affected patients.ResultsAll four patients exhibited typical facial features (such as cupid's bow lip, protruding ears, and thick eyebrows), skeletal abnormalities, and ocular anomalies. Whole-exome sequencing revealed a 16q24.3 microdeletion encompassing the ANKRD11 gene. A literature review identified 68 cases (including the present cases) of KBG syndrome caused by 16q24.3 microdeletions, with a male-to-female ratio of 38:21 (9 cases of unknown sex), including 6 Chinese patients. Non-Chinese patients typically exhibit distinctive facial features including a prominent nasal root (14/28, 50%) and prominent forehead (15/33, 45.45%), whereas Chinese patients display characteristic facial features such as a cupid's bow lip, protruding ears, and thick eyebrows. Among the East Asian population (represented by Chinese individuals), the incidence of prominent eyebrows, cupid's bow lip, and delayed bone age was higher than in other populations. Patients with microdeletions involving only ANKRD11 exhibited a higher prevalence of the characteristic triangular facial appearance and intellectual disability. In this study, the two children received recombinant human growth hormone therapy, achieving catch-up growth with height increases of 1.66 standard deviations and 0.68 standard deviations, respectively.ConclusionThe clinical phenotype of patients with microdeletion-type KBGS mainly includes characteristic facial features, macrodontia, skeletal deformities, neurological abnormalities, and eye deformities. Cupid's bow lip, protruding ears, and thick eyebrows may be characteristic facial features of Chinese children with KBGS. Genetic testing is required for definitive diagnosis. Treatment primarily relies on multidisciplinary teams providing symptomatic supportive care, with the aim of achieving early diagnosis and treatment to improve patient outcomes.